Accuracy of the Intra- and Extra-Oral Scanning Technique for Transferring the Intaglio Surface of a Pontic of Provisional Restorations to Definitive Restorations - Koma Sanda (MDPI AG, 2021)
When taking the final impression for a three-unit fixed partial denture (FPD), the intaglio surface of the pontic of provisional restoration cannot be transferred accurately to that of definitive restoration. The intra- and extra-oral scanning (IEOS) technique, a method for accurately reproducing the submucosal morphology of the superstructure of an implant, has been reported using an intraoral scanner. In the present study, we evaluated the difference between the conventional impression method using impression material and the IEOS technique in reproducing the morphology of the surface of the pontic of a definitive FPD. There was a significant difference in the trueness of the intaglio surface morphology of the pontic between the conventional method and the IEOS technique; however, no significant difference in precision was observed. As a result, the intaglio surface of the pontic of the three-unit FPD could be transferred to definitive restorations more accurately with the IEOS technique than with the conventional method. These results suggest that the IEOS technique can duplicate the intaglio surface of the pontic more reproducibly to the definitive restorations compared with the conventional method.